Morphology and development of the hyolaryngeal apparatus of Pipa arrabali (Anura: Pipidae) - Araujo, O. G. S.; Pugener, L. A.; Haddad, C. F. B. [UNESP]; Da Silva, H. R. (Elsevier B.V., 2017)
Two different perspectives guide ontogenetic studies. On one hand, there is a concern with objective processes and the understanding of the underlying mechanisms that governed the appearance of morphological differences between taxa; on the other hand, there are similarities between ontogenetic patterns that are used as phylogenetic characters. One focus of ontogenetic studies is to understand how morphology and timing of development differ among species. Such studies also aim to serve as a guide in proposing hypotheses of homology, especially when extremely modified structures are under scrutiny, such as the hyobranchial apparatus of amphibians. Here, we describe the morphology and development of the hyobranchial apparatus of Pipa arrabali (based on the examination of 51 embryos and six newly hatched specimens). Its morphology is compared to that described in the literature for other species. In P. arrabali, Copula I is absent, Copula H is present, and the ceratobranchials are simple, without spines or cartilaginous rays. In general, the ontogeny of the hyobranchial apparatus of P. arrabali seems to be accelerated when compared with that of other frogs, with some stages being skipped and the absence of some tadpole-specific structures observed in other species of pipids and non-pipids. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Hyobranchium; Hyoid; Larynx; Ontogeny